Minimally Invasive Breast Biopsies - Brun del Re, Renzo. (Recent Results in Cancer Research,, 2010)
Modern imaging methods have made it possible to detect breast cancer at an earlier stage than in the past. Nevertheless, when screening is performed regularly over a 10-year period, 20% of examined women will present a suspicious finding that subsequently proves to be benign. Accordingly, beyond cancer detection an important goal is the identification of benign lesions in a manner that is reliable, tissue sparing, patient friendly, and cost-effective. More than 70% of breast biopsies can now be performed using minimally invasive procedures that meet these criteria. Against this background, it can be concluded that a mammography screening programme without the possibility of minimally invasive biopsies is neither ethically nor economically justifiable. This book examines in detail the diverse minimally invasive diagnostic techniques that may be employed when imaging yields suspicious findings. These include vacuum-assisted minimally invasive breast biopsy systems (ATEC, EnCor, Intact, Mammotome and Vacora), stereotactic systems, MRI-guided procedures, and ductoscopy. Further chapters are devoted to the pathology of the breast tissue obtained using these procedures, their limitations, the implications of recent advances in breast imaging, and the results of cost-benefit analyses. The closing chapter provides a systematic review and meta-analysis of recent data.